OC-036 A bedside clinical prediction tool can identify eosinophilic oesophagitis in dysphagic adults with a normal endoscopy. (17th June 2017) - Ibraheim, H; Dhillon, A; Kotha, S; Zeki, S
Abstract : Introduction: Eosinophilic oesophagitis (EoE) is an inflammatory condition characterised by symptoms of oesophageal dysfunction (typically dysphagia and food bolus obstruction) and at least 15 eosinophils/hpf on oesophageal biopsy. Although there are endoscopic features associated with EoE, 10%–25% of endoscopies in patients with this condition will be normal [1]. Currently, it is unclear if oesophageal biopsies should be taken in every patient presenting with dysphagia and a normal oesophagus. A more patient focussed strategy can be more cost effective. Our aim was to determine clinical risk factors predictive for EoE, that may then guide the endoscopist for when to take oesophageal biopsies. Method: 127 patients presenting with dysphagia or FBO and a new diagnosis of EoE (eosinophils>15/hpf) were compared to 127 patients presenting with dysphagia or FBO but no evidence of EoE on biopsies. A multivariate logistic regression analysis was carried out to predict who might have EoE prior to taking biopsies, based on history where available and endoscopic findings. Receiver operator characteristic (ROC) curves were generated and the area under the curve (AUC) was calculated to test the accuracy of the model. Results: From the EoE group, 95 (75%) were male and 32 (25%) were female, with an average age of 39 years. From the control group 59 (46%) were male and 68 (54%) were female with an average age of 60 years. The mean number of biopsies taken between the 2 groups was non-significant. In the EoE cohort, the most common abnormal endoscopic findings were strictures (40%) followed by trachealization (15%) and furrows (15%). 19% had a normal endoscopy. A multivariate logistic regression analysis identified age (p<0.001) and sex (p<0.001) as the strongest predictors of EoE. The AUC for younger age and male sex was 0.86 (95% CI 0.81–0.90). Using the Youden index, the optimal cut-off for age was 46 years giving a sensitivity of 86% and specificity of 69%. Conclusion: In patients presenting with dysphagia or FBO and a normal endoscopy, utilising a simple bedside tool comprising of age (<46 years) and male sex can reliably predict the presence of EoE. Reducing the number of potentially low yield histological examinations for EoE has significant implications for time and cost. Reference: . Dellon ES. Diagnostics of eosinophilic esophagitis: clinical, endoscopic, and histologic pitfalls. Dig Dis2014;32(1-2):48–53. Disclosure of Interest: None Declared